A conceptual diagram of homestay stakeholder's interaction in inducing environmental behaviour/ Nur Farihin Abd Hadi Khan ... [et al.] - Abd Hadi Khan, Nur Farihin; Nik Mohd Munir, Nik Madeeha; Muhamad Nasir, Muhamad Nasyat; Mohd Rasdi, Aikal Liyani (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
Previous research studies from many nations have piqued interest in individuals' and organisations' environmental behaviour (EB). EB is defined in this research as any action that is safe or causes insignificant destruction to the environment. There is a shortage of research examining environmental supervision by governing bodies as external stakeholders towards smaller-scale businesses, for instance, the Homestay business. There is still a considerable divergence about environmental behaviour interaction between internal and external stakeholders in the Homestay context. Moreover, it is believed that small businesses like Homestay may face pressures differently from other larger accommodation establishments. By proposing a conceptual diagram relating stakeholder theory (ST) and environmental behaviour (EB), this study consolidates key elements within both contexts, hence proposing the idea that the stakeholder interaction may crucially influence the EB among Homestay operators. It is believed that by observing pertinent research in this emerging field, an in-depth qualitative study to discover EB's real in the Homestay setting can be proposed for future research.